2020
DOI: 10.1002/celc.202001271
|View full text |Cite
|
Sign up to set email alerts
|

A Water‐Splitting System with a Cobalt (II,III) Oxide Co‐Catalyst‐Loaded Bismuth Vanadate Photoanode Along with an Organo‐Photocathode

Abstract: In the water‐splitting reaction, the oxidation of water to O2 is considered to be a kinetically demanding process, so that a co‐catalyst has been usually applied to promote water oxidation. This work demonstrates that, when loading mixed‐valence cobalt (II,III) oxide (Co3O4) dispersed in a Nafion membrane (Nf) on a nanoporous bismuth vanadate (BiVO4) photoanode (i. e., BiVO4/Nf[Co3O4]), stable and efficient water oxidation occurred. In particular, it is noteworthy that the BiVO4/Nf[Co3O4] photoanode exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The efficient kinetics give the GOR a clear advantage in achieving high photocurrents on BVO-based photoanodes in acidic conditions compared to that of the OER. As reported by a previous work, BVO displayed a low photocurrent of about 0.9 mA•cm −2 at 1.2 V versus RHE (pH = 2) with an onset potential of 0.7 V versus RHE for OER, 51 corresponding to our investigation (Figure 2b). The onset potential for the GOR is about 300 mV lower than that for the OER on BVO, indicating the favorable kinetics of the GOR in acidic conditions.…”
Section: Charge Recombination and Hole Transfer Kineticssupporting
confidence: 90%
“…The efficient kinetics give the GOR a clear advantage in achieving high photocurrents on BVO-based photoanodes in acidic conditions compared to that of the OER. As reported by a previous work, BVO displayed a low photocurrent of about 0.9 mA•cm −2 at 1.2 V versus RHE (pH = 2) with an onset potential of 0.7 V versus RHE for OER, 51 corresponding to our investigation (Figure 2b). The onset potential for the GOR is about 300 mV lower than that for the OER on BVO, indicating the favorable kinetics of the GOR in acidic conditions.…”
Section: Charge Recombination and Hole Transfer Kineticssupporting
confidence: 90%
“…The same research group reported in 2020 a photoelectrochemical water-splitting system based on the same Pt loaded ZnPc/C60 bilayer photocathode but using a photoanode comprised with a mixed-valence cobalt( ii , iii ) oxide (Co 3 O 4 ) disperse in a Nafion membrane on a nanoporous BiVO 4 . 315 The stoichiometric generation of H 2 and O 2 occurred by applying a bias voltage as low as 0.1 V, which was superior to the reference system comprising BiVO 4 and Pt, ant the light-to-hydrogen conversion efficiency was ca. 0.08% at 0.6 V. The presence of a cobalt cocatalyst not only improved the water oxidation process but also the stability of the device even in an acidic medium.…”
Section: Phthalocyanines For Photocatalytic H2 Evolutionmentioning
confidence: 96%
“… 16–20 We have been studying organic p–n bilayer, including p-type and n-type, semiconductors for application in photoelectrochemical and photocatalytic reactions in the water phase. 21–32 Some unique reactions, which had not been induced so far by conventional photocatalysts, were also found to occur. 27–32 In our studies, an organic p–n bilayer using 3,4,9,10-perylenetetracarboxylic-bis-benzimidazole (PTCBI) and cobalt phthalocyanine (CoPc) as n-type and p-type semiconductors, respectively, achieved the catalytic oxidation of thiol under illumination and in the dark.…”
Section: Introductionmentioning
confidence: 92%